Pengembangan Budidaya Ikan Air Tawar Rekreatif Di Karanganyar - Setiyawan, Bangkit, Ir. Indrawati, MT (Universitas muhammadiyah Surakarta, 2016)
Karanganyar is a district that enters in Surakarta residency. Karanganyar, Sragen regency on the north, East Java province in the east, Wonogiri and Sukoharjo in the south, and Surakarta and Boyolali regency in the west. Karanganyar administratively consists of 12 villages. The facilities and the development of a recreational freshwater fish farming in Karanganyar should be able to be the inspiration for the spirit of nature conservation. River water flow naturally is the beauty that potential to be developed, but also the conservation points should be at petahankan keaslianya. The addition of elements to the facility as much as possible not interfere with the survival of biological and natural environment there. Therefore, to develop the image of freshwater fish farming penembangan Yeng rekreatif in Karanganyar as a recreation area necessary arrangements to facilitate the activities of this fishery, to create a new tourist attraction that is available to be educational by nature like fish memanfaatkanpotensi object. Expected to be the leading tourism and creating jobs for the local population. Keywords : Aquaculture , Fish , Travel